2021
DOI: 10.1016/j.cdtm.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Self‐management interventions for adults with stroke: A scoping review

Abstract: Background Stroke is a principal cause of mortality and disability globally. Numerous studies have contributed to the knowledge base regarding self-management interventions among chronic disease patients, but there are few such studies for patients with stroke. Therefore, it is necessary to analyze self-management interventions among stroke patients. This scoping review aimed to systematically identify and describe randomized controlled trials (RCTs) of self-management interventions for adults wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Additionally, it was found in this study that although there were only 4 patients diagnosed with their first stroke within 2-6 months, their scores in self-management, medical management, and role management were better than the other 146 patients who were diagnosed within 1 month, which could explain 2.4% of the variance. Furthermore, Ruksakulpiwat and Zhou [36] suggested that the information provided by medical teams to patients who suffered from stroke within 6-12 months could bridge gaps and meet their needs in proactively managing diseases. This is possibly because stroke survivors request more information and medical support from medical experts regarding stroke recovery due to disease progression [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was found in this study that although there were only 4 patients diagnosed with their first stroke within 2-6 months, their scores in self-management, medical management, and role management were better than the other 146 patients who were diagnosed within 1 month, which could explain 2.4% of the variance. Furthermore, Ruksakulpiwat and Zhou [36] suggested that the information provided by medical teams to patients who suffered from stroke within 6-12 months could bridge gaps and meet their needs in proactively managing diseases. This is possibly because stroke survivors request more information and medical support from medical experts regarding stroke recovery due to disease progression [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as described by studies, self-care could significantly improve the physical and mental health outcomes of stroke survivors. 6,7 For example, a systematic review demonstrated that compared with usual care, self-care-related programmes could significantly improve self-efficacy and quality of life in stroke survivors. 8 However, self-care could have an impact not only on stroke survivors but also on their caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, she emphasised the need for refining the definition of self-care to cater to specific diseases and their unique requirements 11. Studies have shown that self-care is of great significance to improve the physical and mental health outcomes (eg, preventing stroke recurrence, reducing readmission rates and improving quality of life) of stroke survivors 12 13. And the improvement of self-care has progressively acted as the core response strategy of the global health system to the increasing burden of stroke 14 15.…”
Section: Introductionmentioning
confidence: 99%